RELATIONSHIP OF FINANCIAL LITERACY AND FINANCIAL PERFORMANCE TO BUSINESS SUSTAINABILITY (STUDY ON MSMEs IN DENPASAR CITY) - Dewi, Ida Ayu Putu Ratna; Candraningrat, Ica Rika (International research journal of management, IT and social sciences, 2022)
This research is an associative quantitative research conducted in Denpasar City. Data consisted of 101 samples, collected by distributing questionnaires. The analysis technique was Structural Equation Model (SEM) by using SmartPLS software. The result showed that financial literacy had a positive and significant effect on the financial performance of MSMEs, financial literacy had a positive and significant effect on the sustainability of MSMEs in Denpasar City, and MSMEs financial performance had a positive and significant effect on the sustainability of MSMEs in Denpasar. This research is expected to be empirical evidence for future research and be able to develop financial management science related to Theory of Planned Behavior, especially financial literacy. The result of the study expressed that financial literacy has an important role for every individual and MSMEs’s subject in order to provide an understanding of finance and in order to improve financial performance to remain stable and have a business sustainability.